Factors predicting pain and early discontinuation of tumour necrosis factor-α-inhibitors in people with rheumatoid arthritis: Results from the British Society for Rheumatology Biologics Register - McWilliams, Daniel F.; Walsh, David A. (BioMed Central, 2016)
Background: We examined pain levels in 2 cohorts assembled from the British Society for Rheumatology Biologics Register (BSRBR), and investigated which factors predicted Bodily Pain scores and discontinuation of TNFα-inhibitors. Method: Data were retrieved from BSRBR-RA databases for up to 1 year after commencing TNFα-inhibitors (n=11995) or being treated with non-biologic therapies (n=3632). Bodily Pain scores were derived from the Short Form-36 (SF36) questionnaire and norm-transformed to allow comparison with UK population averages. Discontinuation data were from physician reports. Other data, including 28-joint disease activity score (DAS28) measurements, were from clinical examination, interview, medical records and self-report questionnaires. DAS28-P was derived as the proportion of DAS28 attributed to patient-reported factors (tender joint count and visual analogue score). Missing baseline variables from both cohorts were imputed into 20 replicate datasets. Odds ratios (OR) and adjusted OR were calculated for higher than median pain within each cohort. Results: Participants reported moderate to severe pain at baseline, and pain scores remained >1SD worse than normal population standards at 1 year, even when disease activity responded to treatment. Baseline pain was associated with DAS28-P, worse physical function, worse mental health, and DAS28. After logistic regression, independent predictors of higher than median pain at follow up were baseline Bodily Pain score, higher DAS28-P, worse physical function or mental health and co-morbidities. Higher age, male gender, and higher BMI were additional independent predictors of higher pain in participants who received TNFα-inhibitors. Baseline pain was also one of the predictors of discontinuation of the first TNFα-inhibitor within 1 year, as were female gender, current smoking, co-morbidities, extra-articular manifestations and worse function. Conclusion: Pain persists in people with treated RA, even in those for whom inflammation responds to treatment. Worse pain outcomes are predicted by factors different to those typically found to predict inflammatory disease activity in other studies. Worse pain at baseline also predicts discontinuation of TNFα-inhibitors. Improved pain management should complement inflammatory disease suppression in RA.